2019
DOI: 10.1155/2019/2046825
|View full text |Cite
|
Sign up to set email alerts
|

Association between Aspartate Aminotransferase-to-Platelet Ratio Index and Hepatocellular Carcinoma Risk in Patients with Chronic Hepatitis: A Meta-Analysis of Cohort Study

Abstract: Background and Aim Aspartate aminotransferase-to-platelet ratio index (APRI) is widely used in the assessment of fibrosis and cirrhosis, especially in patients with chronic hepatitis. However, the prognostic value of APRI in patients with chronic hepatitis with regard to the prediction of hepatocellular carcinoma (HCC) occurrence remains controversial. The objective of this meta-analysis is to investigate the association between APRI and HCC risk on the basis of cohort studies. Methods We systematically review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…Liver stiffness measurement (LSM) has been shown to predict future HCC development in a dose‐dependent manner, with the risk beginning to increase at a threshold of 8 kPa 33,35 . In a recent meta‐analysis, an APRI at cut‐offs ranging from 0.5 to 2.57 also correlate with future HCC development 37 . The expert panel therefore agrees that liver stiffness of ≥8 kPa and/or APRI of ≥1.5 are reasonable indications for anti‐viral therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Liver stiffness measurement (LSM) has been shown to predict future HCC development in a dose‐dependent manner, with the risk beginning to increase at a threshold of 8 kPa 33,35 . In a recent meta‐analysis, an APRI at cut‐offs ranging from 0.5 to 2.57 also correlate with future HCC development 37 . The expert panel therefore agrees that liver stiffness of ≥8 kPa and/or APRI of ≥1.5 are reasonable indications for anti‐viral therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of thromboembolic complications is elevated in individuals during and after influenza virus infection, for example, a relation which may not be apparent to physicians diagnosing and treating influenza-like illness [ 1 ]. Platelet counts during peak symptomatic disease have also been found to be a marker of disease severity in certain viral infections, [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] or can serve as a first clue towards diagnosing chronic viral infections [ 20 , 21 , 22 , 23 ]. These phenomena are typically not explained by changes in platelet quantity, but rather by the effects of viral infections on platelet function.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, aspartate aminotransferase (AST)-to-platelet (PLT) index (APRI) was first proposed by Wai et al as a substitute index for the diagnosis of advanced fibrosis and cirrhosis in the patients with chronic hepatitis C; compared with liver biopsy, APRI is a simple, feasible, and non-invasive predictor and is derived from routine laboratory data calculated as the ratio of [(aspartate aminotransferase/upper limit of normal value)/platelet counts (× 10 9 /L)] × 100 (8)(9)(10). Meta-analysis has revealed that increased APRI levels can predict the risk of HCC development in the patients with chronic hepatitis (11). Furthermore, the preoperative APRI scores are associated with the postoperative complications of HCC and can predict the occurrence of hepatic failure after liver resection (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%